Changes of the glutathione enzymatic redox system in human gastrointestinal tract tumours - Ścibior-Bentkowska, Dorota; Skrzycki, Michał; Podsiad, Małgorzata; Czeczot, Hanna (Archives of Medical Science, 2009)
Introduction: Glutathione (GSH) and GSH-dependent enzymes - glutathione peroxidase (GSHPx), glutathione S-transferase (GST) and glutathione reductase (GSHR) - play a significant role in protecting cells from reactive oxygen species (ROS), which are implicated in tumour disease. The aim of this study was to evaluate reduced glutathione level and GSH-dependent enzyme activities in different types of gastrointestinal tract tumours. Material and methods: We investigated GSH level and GSHPx, GST and GSHR activities in cancer and cancer-free adjacent tissues from patients with gastric (n = 15), liver (n = 30) and colorectal cancer (n = 65), and colorectal cancer liver metastases (n = 50). As a marker of oxidative stress the lipid peroxidation level (expressed as thiobarbituric acid-reactive substances level – TBARS) was determined. Results: Increased level of lipid peroxidation was observed in most of the studied tumours. A significant increase in GSH level was observed exclusively in benign and malignant liver tumours compared to control liver tissue (p Ł 0.05). Activity of studied GSH-dependent enzymes was unchanged in colorectal cancer. Statistically significant differences of those enzymes\' activity in gastric and liver tumours, and colorectal cancer liver metastases compared with control tissues were observed (p Ł 0.05). Conclusions: Changes of lipid peroxidation and GSH levels, and GSH-dependent enzyme activities, suggest that gastrointestinal tract tumours are under the influence of oxidative stress. These results indicate that the glutathione enzymatic redox system is an important mechanism for protection of cancer cells against increased levels of ROS and may point to its role in facilitating development of gastrointestinal tract tumours.